A breath of fresh air: a pilot flipped classroom approach to airway management skills training - Isaac L. Alter; Jonathan Overdevest; Hayley Born; David Liao; Alexandra Michalowski; Vivienne Au; Allison Lin; Nicholas K. Baer; Christopher DiLisio; Elliot Regenbogen (Springer, 2024)
Abstract Objectives While flipped classroom instruction has repeatedly shown efficacy in undergraduate medical education, evidence for its utility in procedural domains remains sparse. This holds particular significance for surgical subspecialties such as otolaryngology, which have limited time in undergraduate medical curricula. We designed a novel airway management skills simulation course with a flipped classroom approach and evaluated its efficacy in a pilot study. Methods A simulation course was designed to provide instruction in seven airway management skills: bag valve mask ventilation, laryngoscopy, intubation, cricothyroidotomy, tracheotomy, and tracheostomy care. Publicly available YouTube videos were selected as pre-learning materials. Participating students completed surveys before the pre-learning assignment and after completion of the simulation center workshop. Results Sixteen students participated in the workshop, and data was collected from 14 participants. Learners reported significant improvements in knowledge regarding all covered skills except tracheotomy; mean self-rated knowledge improved from 2.9 to 5.8 (p < 0.001) on a scale from 0 to 10. Significant increases in self-reported confidence in performing all seven skills were also observed, with an overall increase from 1.1 to 5.7 (p < 0.001). Students also rated all elements of the workshop highly, including a prevailing belief that the pre-learning materials markedly enhanced their learning. Conclusion Our novel framework for skills-based education using a flipped classroom approach demonstrated remarkable efficacy in improving learner knowledge and self-reported confidence regarding airway management skills. This educational design, including the use of high-quality, publicly available pre-learning videos, has significant implications for undergraduate medical education in surgical subspecialties.